2019
DOI: 10.1177/1039856219848832
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of efficacy of Collaborative Assessment and Management of Suicidality (CAMS) in managing suicide risk and deliberate self-harm in adult populations

Abstract: Objective: Evaluate the efficacy of Collaborative Assessment and Management of Suicidality (CAMS) in managing suicide risk and deliberate self-harm in adults. Methods: Ten databases were searched for publications referring to CAMS or the Suicide Status Form. Results were evaluated by two reviewers. Results: Limited evidence that CAMS is effective in reducing suicide risk and deliberate self-harm in adult populations. Conclusions: Although CAMS appears to show promise in managing suicidal patients across a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…A recent review by Hanratty, Kilicaslan, Wilding, and Castle (2019) found limited evidence regarding the effectiveness of Collaborative Assessment and Management of Suicidality in reducing suicide risk and deliberate self-harm in adults. However, evidence from the present review was divided between studies favoring clinician assessment of risk (Quinlivan et al, 2017;Wang et al, 2016), and others where clinician assessment of risk did not significantly predict suicide attempts (Brucker et al, 2019;Harrison et al, 2018), or death from suicide (Randall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Hanratty, Kilicaslan, Wilding, and Castle (2019) found limited evidence regarding the effectiveness of Collaborative Assessment and Management of Suicidality in reducing suicide risk and deliberate self-harm in adults. However, evidence from the present review was divided between studies favoring clinician assessment of risk (Quinlivan et al, 2017;Wang et al, 2016), and others where clinician assessment of risk did not significantly predict suicide attempts (Brucker et al, 2019;Harrison et al, 2018), or death from suicide (Randall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Only one systematic review of CAMS studies has been conducted to date. Hanratty et al (2019) narratively synthesized comparisons of CAMS to alternative interventions in non-retrospective designs (k = 4). The authors concluded that CAMS showed some promise in improving suicidal ideation and some other outcomes, such as hopelessness.…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…While this review (Hanratty et al, 2019) provided an initial examination of CAMS research, it has a number of limitations. First, it did not include RCTs of CAMS that have been published since 2017 (e.g., Jobes et al, 2017;Pistorello et al, 2020;Ryberg et al, 2019).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…13 The Collaborative Assessment and Management of Suicidality approach (an evidencebased therapeutic framework developed three decades ago for the assessment and management of patients at risk for suicide) has been promisingly adapted for delivery via tele-psychotherapy in recent work, although its effectiveness in reducing the risk of suicide and selfharm among adults remains understudied. 14 Clinical experience suggests that virtual risk assessment may need to be modified, particularly with youth, patients with communication challenges, or patients with suspected psychotic symptoms. The authors have begun work to produce a practice guide for virtual and telehealth-based suicide risk assessment and crisis management.…”
Section: Current Evidence and Future Directionsmentioning
confidence: 99%